KEBIJAKAN PEMERINTAH DALAM MEMBINGKAI KEMISKINAN: KONTESTASI RASIONALITAS MODERN DAN EKONOMI MORAL PADA LITERASI FINANSIAL DI INDONESIA - Zakiyudin Fikri; Wahyu Wibowo (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study examines financial literacy in the context of poverty by focusing on the negotiation between state policies and local values within poor communities. Financial literacy is often positioned as a neutral and technocratic instrument to enhance welfare and financial inclusion. However, such an approach frequently overlooks socio-cultural dimensions, power relations, and local economic practices that shape the lived experiences of poverty. This study employs a qualitative approach through a critical literature review of national and international publications from 2020 to 2025, including Scopus- and SINTA-indexed journals as well as relevant policy documents. The analysis is conducted thematically to explore how financial literacy is constructed within state policies, the role of local values, and the forms of negotiation, adaptation, and resistance exhibited by poor communities toward financial literacy programs. The findings indicate that financial literacy has ambivalent effects: while it can enhance financial awareness and access to formal financial services, it may also weaken social solidarity and transform community-based moral economies. Poor communities are not passive recipients of policy interventions but demonstrate agency through the reinterpretation of economic practices and symbolic resistance to individualistic approaches. This study highlights the importance of a policy anthropology perspective in designing culturally sensitive and contextually grounded financial literacy policies as part of sustainable poverty alleviation efforts.